Correlation of Anthropometric Measurements with Blood Pressure among Medical students in Karnataka - Nimisha V, Vinod Rathod D, Amrut Arvindrao Dambal*, Kusuma N (Journal of Neonatal Surgery, 2025)
Introduction: The prevalence of obesity is increasing at an alarming rate. One of the regions with rapidly increasing rate of overweight and obesity is the South Asian region. Obesity is an important risk factor for cardiovascular diseases caused due to hypertension and diabetes. This study calls attention to the importance of Anthropometric measurements in assessment of Blood Pressure among medical students. Methods: 170 medical students were included in this cross sectional observational study. Blood pressure and various anthropometric measurements like Body Mass Index (BMI, Waist Circumference (WC). Hip Circumference (HC), Waist to Hip ratio (WHR) and Waist to Height Ratio (WHtR) were measured. The students were categorized into various categories based on Asian Guidelines for Classification of Obesity. Also they were categorized into Blood Pressure classes based on SBP and DBP values. Results: Out of 170 medical students including 110 males and 70 females, it was found that 11.8 % students were overweight and 18.3 % students were obese. 63.5 % students had normal Blood Pressure (<120/<80 mmHg), 22.9 % had elevated Blood Pressure (120-129/<80mmHg) and 13.5% students were found to have Hypertension Stage 1 (130-139/80-89 mm Hg). There was no significant difference between males and females with regards to mean of BMI, WC, HC, WHR, WHtR, SBP and DBP. A statistically significant correlation of SBP was found with BMI (r=0.436, p=0.001), WC (r=0.498, p=0.001), WHtR (r= 0.350, p=0.001), WHR (r=0.417, p=0.001). BMI, WC, WHtR and WHR were found to be significantly higher in group of students in Hypertension stage 1 compared to normal and elevated stages. Conclusion: Obesity prevalence in our study was found to 18.3 %. The prevalence of Stage 1 Hypertension was found to be 13.5%. The values of systolic and diastolic blood pressure were found to be different across anthropometric indices (BMI, WC, WHR, WHtR).